Descriptive Study of Merdeka Curriculum Implementation at SDN 1 Telaga Biru - Nurmila Husain; Lia Nurhayati; Yusraningsih Pongoliu (Journal of Education Review Provision, 2023)
The objective of the independent curriculum is to find out the results of the implementation of the independent curriculum at SDN 1 Telaga Biru. This research used a qualitative descriptive method, the informants were one school principal, two educators and five students. This research is to find out about how the implementation of the independent curriculum at SDN 1 Telaga Biru. Several techniques were used in data collection, namely: a) Observation, b) Interview, c) Documentation. The results show that in the implementation of the independent curriculum there is more emphasis on substantive material and developing student competencies according to the stages. Therefore, learning with this independent curriculum is expected to be more in-depth, not rushed, more fun and meaningful. Thus, the implementation of the Independent Curriculum is more optimal even though it has only been implemented for one year. The Independent Curriculum, still needs to be developed and improved thus it can overcome current educational problems.